Activated carbon and its impurity removal method and application in preparing electronic grade sulfate

The three-stage cleaning method removes activated carbon, which solves the problem that the purity and impurity content of electronic grade copper sulfate in the prior art is difficult to meet the requirements, and realizes the preparation of activated carbon with high purity and low impurity, which is suitable for the efficient preparation of electronic grade sulfates.

CN118954508BActive Publication Date: 2025-04-25FANGYUAN ENVIRONMENG CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410891237.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-04-25
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The existing oxidative neutralization method is difficult to achieve high purity and low impurity content when preparing electron-grade copper sulfate, especially high total organic carbon (TOC) content, and untreated activated carbon contains a large amount of impurities, which affects the impurity removal effect.

Method used

The third-level cleaning method is used to remove impurities of activated carbon, including the first-level cleaning using dilute sulfuric acid, the second-level cleaning using ultrapure water, and the third-level cleaning using sulfate solution. Through these steps, metal impurities and organic pollutants in the activated carbon are gradually removed.

Benefits of technology

The obtained activated carbon has high purity, low metal impurity content and good TOC removal effect. It is suitable for the preparation of high purity electronic grade sulfates, which significantly improves the quality and purity of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954508B_ABST
    Figure CN118954508B_ABST
Patent Text Reader

Abstract

The present invention discloses an activated carbon and its impurity removal method and application in the preparation of electronic grade sulfate. The impurity removal method of activated carbon provided by the present invention comprises the following steps: S1, primary cleaning: using dilute sulfuric acid to clean the activated carbon raw material and soaking for 20 to 30 hours to obtain primary activated carbon; S2, secondary cleaning: using ultrapure water to clean the primary activated carbon to obtain secondary activated carbon and water washing liquid, the conductivity of the water washing liquid is ≤10μS; S3, tertiary cleaning: using sulfate solution to clean the secondary activated carbon to obtain activated carbon and sulfate washing liquid after impurity removal, the difference between the total content of metal impurities in the sulfate washing liquid and the total content of metal impurities in the sulfate solution is ≤30μg / L. The present invention uses a three-stage cleaning method to remove impurities from the activated carbon raw material, and the total content of metal impurities in the activated carbon after impurity removal is low. It has a good effect when used in the preparation process of electronic grade sulfate, especially can achieve a good TOC removal effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical processes, and in particular relates to activated carbon and an impurity removal method thereof, and application thereof in the preparation of electronic grade sulfate. Background Art

[0002] With the rapid development of the electronics industry, especially the continuous advancement of semiconductor and integrated circuit manufacturing technology, the purity and quality requirements for electronic-grade chemicals are becoming increasingly higher. As one of the key electronic chemicals, electronic-grade sulfate plays a vital role in the manufacturing process of electronic devices. Electronic-grade sulfate needs to have extremely high purity and low impurity content to meet the strict requirements of the electronics industry for chemicals. Electronic-grade sulfates include copper sulfate, cobalt sulfate, nickel sulfate, manganese sulfate, zinc sulfate, etc. They are widely used in cleaning, etching, electroplating and as catalysts for certain chemical reactions.

[0003] Take copper sulfate as an example, it is an important copper salt in copper compounds, which is widely used in the chemical industry, such as electroplating, catalysis and preparation of chemicals, etc. With the rapid development of electroplating industry and printed circuit board industry, the demand for copper sulfate has increased rapidly, and strict requirements have been put forward for the quality of copper sulfate products. Since the crude copper sulfate of industrial grade inevitably contains organic impurities, various metal and non-metallic impurities to varying degrees, the use of these impurities without removing them will seriously affect the quality of electronic products, for example, it will cause the phenomenon of reducing the plating speed, darkening of the coating, plating leakage, and deposition on the coating, causing the coating to be unstable, making the coating rough, etc. Therefore, electronic grade copper sulfate has become a key electronic chemical in the electronics industry. Similarly, the preparation of other high-purity electronic grade sulfates is also an important problem that needs to be solved in this area.

[0004] At present, the main methods for producing electronic grade sulfate include oxidation neutralization, electrolysis, recrystallization and extraction. Among them, oxidation neutralization is an easy-to-operate, low-cost and highly efficient method, but the copper sulfate product obtained by the current oxidation neutralization method has low purity, high content of metal impurities and organic impurities, especially high content of total organic carbon (TOC), and it is difficult for the oxidation neutralization method to achieve a good TOC removal effect. Some studies have proposed the use of activated carbon for adsorption and impurity removal, but activated carbon contains a large amount of impurities, especially high content of calcium and magnesium, and it is difficult to achieve a good impurity removal effect using untreated activated carbon. Summary of the invention

[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a method for removing impurities from activated carbon. Through specific impurity removal steps, activated carbon with high purity and low metal impurity content can be obtained, which can be used to prepare high-purity electronic grade sulfate.

[0006] A second object of the present invention is to provide activated carbon obtained by the above impurity removal method.

[0007] A third object of the present invention is to provide an application of the above-mentioned activated carbon in the preparation of electronic grade sulfate.

[0008] A fourth object of the present invention is to provide a method for preparing electronic grade sulfate using the above-mentioned activated carbon.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] The first aspect of the present invention provides a method for removing impurities from activated carbon, comprising the following steps:

[0011] S1. Primary cleaning: Use dilute sulfuric acid to clean the activated carbon raw material and soak it for 20 to 30 hours to obtain primary activated carbon;

[0012] S2. Secondary cleaning: using ultrapure water to clean the primary activated carbon to obtain secondary activated carbon and a washing liquid, wherein the conductivity of the washing liquid is ≤10 μS;

[0013] S3, tertiary cleaning: the secondary activated carbon is cleaned with a sulfate solution to obtain activated carbon and sulfate washing solution after impurities are removed, the difference between the total content of metal impurities in the sulfate washing solution and the total content of metal impurities in the sulfate solution is ≤30 μg / L; the metal impurities include other metal elements except the metal elements in the sulfate.

[0014] The present invention adopts a three-stage cleaning step to remove impurities from the activated carbon. First, dilute sulfuric acid is used for full cleaning to soak out some acid-soluble metal impurities. Then, ultrapure water is used for cleaning to further remove impurities and residual acid solution is washed away to avoid affecting subsequent steps. Finally, sulfate solution is used for cleaning. Since metal ions (such as Cu ions, Co ions, Ni ions, Mn ions, Zn ions, etc.) in the sulfate solution are relatively front in the activated carbon adsorption order, they can replace the metal impurities adsorbed in the activated carbon, so that the metal impurities are desorbed from the activated carbon, thereby achieving the effect of further purification of the activated carbon column. The difference between the total content of metal impurities in the sulfate washing solution and the total content of metal impurities in the sulfate solution is ≤30μg / L.

[0015] The sulfate washing liquid after the third-level cleaning was tested to be qualified, indicating that during the adsorption process, the impurities could no longer be desorbed from the activated carbon. The gold impurities in the sulfate washing liquid were qualified, indicating that the activated carbon had been cleaned and achieved a good impurity removal and purification effect.

[0016] In some embodiments of the present invention, in step S3, the sulfate includes copper sulfate, cobalt sulfate, nickel sulfate, manganese sulfate or zinc sulfate. In some specific embodiments of the present invention, the type of sulfate used in step S3 is the same as the type of electronic grade sulfate prepared subsequently.

[0017] In some embodiments of the present invention, in step S1, the activated carbon raw material is a wood activated carbon raw material.

[0018] In some embodiments of the present invention, wood activated carbon raw materials are specifically used, which are made from wood raw materials. Compared with coal-based activated carbon made from coal-based raw materials, wood activated carbon has fewer metal impurities and is more suitable for the impurity removal method of the present invention. The wood activated carbon after impurity removal has a good adsorption effect on organic pollutants, which is conducive to the preparation of high-purity electronic-grade sulfate.

[0019] In some embodiments of the present invention, in step S1, the concentration of the dilute sulfuric acid is 0.01 to 10 mol / L; in some embodiments of the present invention, the concentration of the dilute sulfuric acid is 0.03 to 5 mol / L; non-limiting examples are 0.05 mol / L, 0.1 mol / L, 1 mol / L or 3 mol / L.

[0020] In some embodiments of the present invention, in step S2, the conductivity of the ultrapure water is ≤1 μS; in some specific embodiments of the present invention, the conductivity of the ultrapure water is 0.1-1 μS; non-limiting examples are 0.3 μS, 0.5 μS, 0.7 μS or 0.9 μS.

[0021] In some embodiments of the present invention, in step S2, the total content of metal impurities in the ultrapure water is ≤10 μg / L; in some specific embodiments of the present invention, the total content of metal impurities in the ultrapure water is 4-10 μg / L; non-limiting examples are 5 μg / L, 6 μg / L, 7 μg / L, 8 μg / L or 9 μg / L.

[0022] In some embodiments of the present invention, in step S1, the volume ratio of dilute sulfuric acid to activated carbon is not limited, as long as the dilute sulfuric acid can immerse the activated carbon.

[0023] In some embodiments of the present invention, in step S2, the volume ratio of ultrapure water to activated carbon is not limited.

[0024] In some embodiments of the present invention, in step S3, the volume ratio of sulfate solution to activated carbon is (5-20):1; in some specific embodiments of the present invention, the volume ratio of sulfate solution to activated carbon is (6-15):1; non-limiting examples are 7:1, 8:1, 10:1 or 12:1.

[0025] In some embodiments of the present invention, before cleaning, the step of filling activated carbon raw materials into an activated carbon column is also included. The activated carbon column has openings at both ends, divided into an upper opening and a lower opening, for liquid to enter and exit.

[0026] In some embodiments of the present invention, the dilute sulfuric acid in step S1 flows into the upper opening of the activated carbon column and flows out of the lower opening; the ultrapure water in step S2 flows into the upper opening of the activated carbon and flows out of the lower opening; the sulfate solution in step S3 flows into the lower opening of the activated carbon column and flows out of the upper opening.

[0027] The first and second stage cleaning both adopt the forward wash with top in and bottom out, while the third stage cleaning adopts the backwash with bottom in and top out. The third stage cleaning adopts the bottom in and top out method, which can maintain a specific volume ratio of sulfate solution and activated carbon, so that the sulfate solution can fully clean the activated carbon and the impurity removal effect is better.

[0028] In some embodiments of the present invention, in step S3, the metal ion concentration of the sulfate solution is 50-80 g / L; non-limiting examples are 55 g / L, 60 g / L, 65 g / L, 70 g / L or 75 g / L.

[0029] The second aspect of the present invention provides activated carbon obtained by the impurity removal method described in the first aspect of the present invention.

[0030] The activated carbon obtained by the impurity removal method according to the first aspect of the present invention has high purity and low content of metal impurities.

[0031] The third aspect of the present invention provides a use of the activated carbon described in the second aspect of the present invention in the preparation of electronic grade sulfate.

[0032] The activated carbon described in the second aspect of the present invention has a low content of metal impurities and will not introduce new metal impurities when used to prepare electronic-grade sulfate. The wood activated carbon after impurities removal has a good adsorption effect on organic pollutants, which is beneficial to effectively reduce the total organic carbon (TOC) content in the sulfate product. When the activated carbon is used to prepare electronic-grade sulfate, it is beneficial to obtain electronic-grade sulfate with high purity, low metal impurity content and low TOC content.

[0033] The fourth aspect of the present invention provides a method for preparing electronic-grade sulfate, comprising the following steps: passing a crude sulfate solution through an activated carbon column containing the activated carbon described in the second aspect of the present invention to remove oil and obtain a sulfate deoiled liquid; and crystallizing the sulfate deoiled liquid to obtain the electronic-grade sulfate.

[0034] In some embodiments of the present invention, the process further comprises dissolving the electronic grade sulfate to prepare an electronic grade sulfate solution. The solvent used for the dissolution is preferably pure water, more preferably ultrapure water.

[0035] In some embodiments of the present invention, during oil removal, the residence time of the crude sulfate solution in the activated carbon column is 0.6 to 5 hours; in some specific embodiments of the present invention, the residence time of the crude sulfate solution in the activated carbon column is 0.8 to 3 hours; non-limiting examples are 0.9 hours, 1 hour, 1.2 hours, 1.5 hours, 2 hours or 2.5 hours.

[0036] The activated carbon provided by the present invention has a good adsorption effect on TOC contained in a crude sulfate solution. When the residence time is above 0.6h, the TOC removal rate can reach above 60%, and can reach above 80% after a residence time of about 1h. Electronic grade sulfate with a low TOC content can be obtained by adjusting the residence time. The method is simple, efficient and has a good purification effect.

[0037] In some embodiments of the present invention, during oil removal, the pH value of the crude sulfate solution is adjusted to 2-5; in some specific embodiments of the present invention, the pH value of the crude sulfate solution is adjusted to 2-4.5; non-limiting examples are 2.2, 2.5, 3, 3.2, 3.5, 3.9 or 4.

[0038] After cleaning and modification, the activated carbon has functional groups such as hydroxyl and carboxyl attached to its surface. As the pH changes, the activated carbon's adsorption capacity for organic molecules will also change. Therefore, when the crude sulfate solution is adjusted to an appropriate pH value, the activated carbon has a good adsorption and removal effect on TOC. When the pH is too high, the TOC removal rate will decrease, and the metal ions in the solution will easily precipitate, causing product loss. When the pH is low, the effect of improving the TOC removal rate is not obvious, and it will also lead to excessive acid consumption and increase costs.

[0039] In some embodiments of the present invention, when the sulfate is copper sulfate, during oil removal, the pH value of the crude sulfate solution is adjusted to 2-4.5; non-limiting examples are 2.2, 2.5, 3, 3.2, 3.5 or 4.

[0040] In some embodiments of the present invention, when the sulfate is cobalt sulfate, during oil removal, the pH value of the crude sulfate solution is adjusted to 2.8-4.4; non-limiting examples are 3, 3.2, 3.5, 3.8, 4 or 4.2.

[0041] In some embodiments of the present invention, the activated carbon is granular activated carbon, and the average particle size of the granular activated carbon is 0.5-3 mm; in some specific embodiments of the present invention, the average particle size of the granular activated carbon is 0.7-2.5 mm; non-limiting examples are 0.8 mm, 1 mm, 1.5 mm or 2 mm.

[0042] The use of granular activated carbon can bring it into contact with the crude sulfate solution more fully, and the specific particle size has a better adsorption effect on impurities, thereby achieving a good purification effect.

[0043] In some embodiments of the present invention, the specific surface area of ​​the activated carbon is 1000-1500m 2 / g; a non-limiting example is 1100m 2 / g、1200m 2 / g、1300m 2 / g or 1400m 2 / g.

[0044] The beneficial effects of the present invention are as follows: the present invention adopts a three-stage cleaning method to remove impurities from the activated carbon raw material, and the total content of metal impurities in the obtained activated carbon is low. The activated carbon used in the preparation process of electronic-grade sulfate has a good effect, especially can achieve a good TOC removal effect. The activated carbon obtained by the impurity removal method of the present invention has a wide range of applications in the preparation of high-purity electronic-grade sulfate. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The present invention is a process flow chart of the activated carbon impurity removal method in some embodiments of the present invention.

[0046] Figure 2 The present invention is a process flow chart of the method for removing impurities from activated carbon in Example 1. DETAILED DESCRIPTION

[0047] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0048] The activated carbon raw material of the present invention contains a large amount of metal ions. In some embodiments of the present invention, the metal ions in the activated carbon raw material include at least one of copper, calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, cobalt, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium or thallium; in some specific embodiments of the present invention, the metal ions in the activated carbon raw material include copper, calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, titanium, cobalt, zinc, arsenic, zirconium and lead; in some examples of the present invention, among the metal ions in the activated carbon raw material, the calcium content is 300-400 mg / kg, the magnesium content is 200-300 mg / kg, the potassium content is 7000-8000 mg / kg, and the sodium content is 700-800 mg / kg.

[0049] Some embodiments of the present invention provide a method for removing impurities from activated carbon, the process diagram of which is as follows: Figure 1 As shown, the following steps are included:

[0050] S1. Primary cleaning: Use dilute sulfuric acid to clean the activated carbon raw material and soak it for 20 to 30 hours to obtain primary activated carbon;

[0051] S2. Secondary cleaning: using ultrapure water to clean the primary activated carbon to obtain secondary activated carbon and a washing liquid, wherein the conductivity of the washing liquid is ≤10 μS;

[0052] S3, tertiary cleaning: the secondary activated carbon is cleaned with a sulfate solution to obtain activated carbon and sulfate washing solution after impurities are removed, the difference between the total content of metal impurities in the sulfate washing solution and the total content of metal impurities in the sulfate solution is ≤30 μg / L; the metal impurities include other metal elements except the metal elements in the sulfate.

[0053] In some embodiments of the present invention, in step S3, the sulfate includes copper sulfate, cobalt sulfate, nickel sulfate, manganese sulfate or zinc sulfate. In some specific embodiments of the present invention, the type of sulfate used in step S3 is the same as the type of electronic-grade sulfate prepared subsequently, for example, for example, if the activated carbon after impurities removal is used to prepare electronic-grade copper sulfate, the sulfate used in step S3 is copper sulfate; or if the activated carbon after impurities removal is used to prepare electronic-grade cobalt sulfate, the sulfate used in step S3 is cobalt sulfate, and so on.

[0054] In some embodiments of the present invention, the metal impurities include at least one of copper, calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, cobalt, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium or thallium, and do not include metal elements in sulfate. For example, when the sulfate in step S3 is copper sulfate, the metal impurities include at least one of calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, cobalt, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium or thallium (excluding copper); when the sulfate in step S3 is cobalt sulfate, the metal impurities include at least one of copper, calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium or thallium (excluding cobalt).

[0055] The invention is described below with reference to specific embodiments and comparative examples.

[0056] In the following examples, ND means that when the content of a substance is lower than the minimum detection limit of the detection equipment, the substance will be marked as "ND" in the test report, indicating that the content of the substance is ≤0.01μg / L. Gold impurities refer to metal impurities, and total gold impurities refer to the total content of metal impurities.

[0057] Example 1

[0058] This example provides a method for removing impurities from activated carbon. The process flow chart is as follows: Figure 2 As shown, the specific steps include:

[0059] S1. Primary cleaning: Fill the activated carbon raw material into the activated carbon column. The two ends of the activated carbon column are open, divided into upper opening and lower opening, for liquid to enter and exit. Dilute sulfuric acid is passed through the upper opening to clean the activated carbon raw material and soak for 20 to 30 hours. The dilute sulfuric acid washing liquid flows out from the lower opening, and the activated carbon column contains primary activated carbon.

[0060] Since the activated carbon in this example is used for the preparation of electronic grade copper sulfate, the metal ions other than copper ions are all metal impurities, that is, in this example, the metal impurities refer to calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, cobalt, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium and thallium (excluding copper), and the total metal impurity content refers to the comprehensive content of the above metal impurities.

[0061] The activated carbon raw material in step S1 is specifically commercially available wood activated carbon raw material, and the metal impurities contained in it are shown in Table 1. Compared with coal-based activated carbon prepared from coal-based raw materials, wood activated carbon has fewer metal impurities and is suitable for the impurity removal method of the present invention. The wood activated carbon after impurity removal has a good adsorption effect on organic pollutants, which is conducive to the preparation of high-purity electronic grade sulfate.

[0062] Table 1 Metal impurities in wood activated carbon raw materials

[0063]

[0064]

[0065] S2, secondary cleaning: Ultrapure water is introduced from the upper opening of the activated carbon column to clean the primary activated carbon, and the washing liquid flows out from the lower opening until the conductivity of the washing liquid is ≤10μS. The activated carbon column contains secondary activated carbon. The conductivity of the ultrapure water used in this step is 0.95μS, and the total content of metal impurities in the ultrapure water is 9.44μg / L. The metal impurities detected in the ultrapure water are: 4.79μg / L Ca, 1.49μg / L Ni, 1.46μg / L Sn and 1.70μg / L Zn, and no other metal impurities are detected.

[0066] After the secondary cleaning, the metal impurities and their contents in the water washing liquid are shown in Table 2. It can be seen that after the primary and secondary cleaning, the washing liquid contains less metal impurities, and will not bring too many metal impurities into the washing liquid when used for adsorption and oil removal.

[0067] Table 2 Metal impurities in the water wash solution after secondary cleaning

[0068]

[0069] S3. Tertiary cleaning: copper sulfate solution is introduced into the lower opening of the activated carbon column to clean the secondary activated carbon, and copper sulfate washing liquid flows out of the upper opening. The volume ratio of copper sulfate solution to activated carbon is shown in Table 3. The residence time of copper sulfate solution in the carbon column is controlled to be 1 hour. The copper sulfate solution is used for cleaning until the difference between the total content of metal impurities in the copper sulfate washing liquid and the total content of metal impurities in the copper sulfate solution is ≤30 μg / L, thereby obtaining activated carbon after impurity removal.

[0070] The comparison of the removal effect of metal impurities at different volume ratios of copper sulfate solution to activated carbon is shown in Table 3. The copper ion concentration of the copper sulfate solution in this step is 50 g / L. The copper sulfate solution of this concentration has a good cleaning effect on metal impurities, and can wash out metal impurities in activated carbon. Finally, the difference between the total content of metal impurities in the copper sulfate washing solution and the total content of metal impurities in the sulfate solution is reduced to 30 μg / L or less.

[0071] Table 3 Comparison of metal impurities at different volume ratios of copper sulfate solution and activated carbon

[0072]

[0073] Note: Total gold impurities are the combined content of calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, cobalt, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium and thallium.

[0074] The copper sulfate solution itself contains trace amounts of metal impurities before washing. The specific metal impurities and their contents are shown in Table 4. The metal impurity contents in the copper sulfate washing solution after the three-stage washing in this example are shown in Table 5, wherein the volume ratio of the copper sulfate solution to the activated carbon is 8:1.

[0075] After the secondary cleaning, ultrapure water can no longer wash away the metal impurities adsorbed on the activated carbon, and the cleaning limit of ultrapure water for activated carbon has been reached (22.88μg / L). However, some metal impurities are still adsorbed on the activated carbon, and copper sulfate solution is needed for cleaning. The Cu ions in the copper sulfate solution are relatively advanced in the activated carbon adsorption order, which can replace the metal impurities adsorbed in the activated carbon, so that the gold impurities are desorbed from the activated carbon, thereby achieving the effect of further purification of the activated carbon column. The copper sulfate washing solution after the tertiary cleaning is qualified, indicating that during the adsorption process, the impurities can no longer be desorbed from the carbon column. The gold impurities in the copper sulfate washing solution are qualified, indicating that the carbon column has been cleaned and a good impurity removal and purification effect has been achieved.

[0076] Table 4 Metal impurities in copper sulfate solution before tertiary cleaning

[0077]

[0078] Table 5 Metal impurities in copper sulfate washing solution after three-stage cleaning

[0079]

[0080] Application Example 1

[0081] This example provides a method for preparing electronic grade copper sulfate, which specifically comprises the following steps:

[0082] Take an activated carbon column filled with activated carbon, the actual column length is 175-185 cm, the effective column length is 150-160 cm, the activated carbon is the activated carbon obtained after impurities are removed in Example 1, and its specific surface area is 1300m 2 / g, in granular form with a particle size in the range of 0.83 to 2.36 mm, into which a crude copper sulfate solution is introduced at a flow rate of 50 L / h for degreasing to obtain a copper sulfate degreasing liquid; the copper sulfate degreasing liquid is crystallized to obtain electronic grade copper sulfate; ultrapure water is then added for dissolution, and an electronic grade copper sulfate solution is obtained after packaging.

[0083] During oil removal, the pH value of the copper sulfate crude solution was changed and the TOC removal rate was measured, as shown in Table 6. In this process, sulfuric acid or ammonia water was used to adjust the pH value, and the residence time of the copper sulfate crude solution in the activated carbon column was 1 hour.

[0084] Table 6 Relationship between pH value of copper sulfate crude solution and TOC removal rate

[0085]

[0086]

[0087] It can be seen from Table 6 that when the pH value of the copper sulfate crude solution is between 2 and 4.5, it has a good TOC removal effect. As the pH value increases, the TOC removal rate decreases. When the pH value is 3.8, the removal rate is high and can reach more than 93%. When the pH value is further reduced, the TOC removal effect is not obvious.

[0088] During oil removal, the residence time of the copper sulfate crude solution in the activated carbon column was changed and the TOC removal rate was measured, as shown in Table 7. In this process, the pH value of the copper sulfate crude solution was 3.8.

[0089] Table 7 Relationship between the residence time of copper sulfate crude solution in the activated carbon column and TOC removal rate

[0090]

[0091] As can be seen from Table 7, when the residence time of the copper sulfate crude solution in the activated carbon column is 0.6 to 2 hours, it has a good TOC removal effect. When the residence time is above 0.6 hours, the TOC removal rate can reach more than 70%, and it can reach more than 90% when it stays for 1 hour. Extending the residence time beyond 1 hour has no obvious effect on TOC removal, mainly because the adsorption capacity of the activated carbon at this time is close to saturation. When the residence time is 1 hour, a good TOC removal rate can be achieved, which can reach about 93%. It can be seen that the method of using the activated carbon of Example 1 in Application Example 1 to remove TOC is simple, efficient and has a good purification effect.

[0092] The obtained electronic-grade copper sulfate is tested to obtain a purity of 99.9998%. In the electronic-grade copper sulfate solution with Cu=80g / L, the total content of metal impurities such as Fe, Ti, Al, and Ca is below 1mg / L, wherein the Fe content is ≤110μg / L, the Ti content is ≤110μg / L, and the TOC content is ≤2mg / L. The method of Application Example 1 can obtain electronic-grade copper sulfate with high purity and low impurity content, which can be used as a product in the field of nano-scale chip integrated circuits, especially using the activated carbon obtained in Example 1 for adsorption and oil removal, achieving a good TOC removal effect, and will not introduce new metal impurities, thereby ensuring the purity of the final product.

[0093] Application Comparative Example 1

[0094] This example provides a method for preparing electronic-grade copper sulfate. The difference from Application Example 1 is that the activated carbon filled in the activated carbon column of this example is commercially available, unwashed wood activated carbon raw material; the pH value of the copper sulfate crude solution is 3.8, and the residence time of the copper sulfate crude solution in the activated carbon column is 1 hour.

[0095] The purity of the electronic-grade copper sulfate obtained in this example is 99.992%. In the electronic-grade copper sulfate solution with Cu=80g / L, the total content of metal impurities such as Fe, Ti, Al, and Ca is 21.38mg / L, and the TOC content is 3mg / L. It can be seen that directly using unwashed wood activated carbon raw materials for adsorption and oil removal will introduce more impurities, making it difficult to prepare high-purity electronic-grade copper sulfate.

[0096] Application Comparative Example 2

[0097] This example provides a method for preparing electronic grade copper sulfate. The difference from Application Example 1 is that this example does not use an activated carbon column for oil removal.

[0098] The purity of the electronic-grade copper sulfate obtained in this example is 99.997%. In the electronic-grade copper sulfate solution with Cu=80g / L, the total content of metal impurities such as Fe, Ti, Al, Ca is 0.9mg / L, and the TOC content is 20.367mg / L. It can be seen that the removal effect of TOC is poor when activated carbon is not used for adsorption and oil removal; while the total content of metal impurities in Application Example 1 is basically the same as that in Application Comparative Example 2, that is, Application Example 1 uses activated carbon after impurities removal for adsorption and oil removal, which does not introduce additional metal impurities into the system and can achieve a better TOC removal effect.

[0099] Example 2

[0100] This example provides a method for removing impurities from activated carbon. The difference from Example 1 is that step S3 is different. Step S3 of this example is:

[0101] S3. Tertiary cleaning: cobalt sulfate solution is introduced from the lower opening of the activated carbon column to clean the secondary activated carbon, and cobalt sulfate washing solution flows out from the upper opening. The volume ratio of cobalt sulfate solution to activated carbon is 8:1. The residence time of cobalt sulfate solution in the carbon column is controlled to be 1h. The cobalt sulfate solution is used for cleaning until the difference between the total content of metal impurities in the cobalt sulfate washing solution and the total content of metal impurities in the sulfate solution is ≤30μg / L, so as to obtain activated carbon after impurity removal.

[0102] In this example, the metal impurities refer to copper, calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium and thallium (excluding cobalt), and the total metal impurity content refers to the comprehensive content of the above metal impurities.

[0103] Application Example 2

[0104] This example provides a method for preparing electronic grade cobalt sulfate, which specifically comprises the following steps:

[0105] Take an activated carbon column filled with activated carbon, the actual column length is 175-185 cm, the effective column length is 150-160 cm, the activated carbon is the activated carbon obtained after impurities are removed in Example 2, and its specific surface area is 1300m 2 / g, in granular form with a particle size in the range of 0.83 to 2.36 mm, into which a crude cobalt sulfate solution is introduced at a flow rate of 50 L / h for degreasing to obtain a cobalt sulfate degreasing liquid; the cobalt sulfate degreasing liquid is crystallized to obtain electronic grade cobalt sulfate, ultrapure water is added for dissolution, and an electronic grade cobalt sulfate solution is obtained after packaging.

[0106] During oil removal, the pH value of the crude cobalt sulfate solution was changed and the TOC removal rate was measured, as shown in Table 8. In this process, sulfuric acid or ammonia water was used to adjust the pH value, and the residence time of the crude cobalt sulfate solution in the activated carbon column was 1 hour.

[0107] Table 8 Relationship between pH value of crude cobalt sulfate solution and TOC removal rate

[0108]

[0109] It can be seen from Table 8 that when deoiling, when the pH value of the crude cobalt sulfate solution is between 2.8 and 4.4, it has a good TOC removal effect. As the pH value increases, the TOC removal rate decreases. When the pH value is 3.2, the removal rate is high and can reach more than 88%. When the pH value is further reduced, the TOC removal effect is not obvious.

[0110] During oil removal, the residence time of the crude cobalt sulfate solution in the activated carbon column was changed and the TOC removal rate was measured. As shown in Table 9, the pH value of the crude cobalt sulfate solution was 3.2 during the process.

[0111] Table 9 Relationship between the residence time of crude cobalt sulfate solution in the activated carbon column and TOC removal rate

[0112]

[0113] As can be seen from Table 9, when the residence time of the crude cobalt sulfate solution in the activated carbon column is 0.6 to 2 hours, it has a good TOC removal effect. When the residence time is above 0.6 hours, the TOC removal rate can reach more than 60%, and it can reach more than 84% when it stays for 1 hour, and it can reach more than 87% when it stays for 1.5 hours. Extending the residence time beyond 1 hour has no obvious effect on TOC removal, mainly because the adsorption capacity of activated carbon at this time is close to saturation. When the residence time is 2 hours, a good TOC removal rate can be achieved, which can reach more than 88%. It can be seen that the method of using the activated carbon of Example 2 in Application Example 2 for TOC removal is simple, efficient and has a good purification effect.

[0114] In this example, the metal impurities refer to copper, calcium, magnesium, lithium, sodium, potassium, aluminum, chromium, manganese, iron, nickel, tin, titanium, zinc, arsenic, zirconium, silver, cadmium, gold, lead, mercury, indium and thallium (excluding cobalt), and the total metal impurity content refers to the comprehensive content of the above metal impurities.

[0115] The obtained electronic-grade cobalt sulfate was tested and its purity was 99.998%. In the electronic-grade cobalt sulfate solution, the total content of metal impurities such as Fe, Ti, Al, and Ca was below 1.4 mg / L. The method of Application Example 2 can obtain electronic-grade cobalt sulfate with high purity and low impurity content, which can be used as a product in the field of nano-chip integrated circuits. In particular, the activated carbon obtained in Example 2 is used for adsorption and oil removal, which achieves a good TOC removal effect, and does not introduce new metal impurities, thereby ensuring the purity of the final product.

[0116] Similarly, the present invention is also applicable to the preparation of other electronic-grade sulfates, such as nickel sulfate, manganese sulfate or zinc sulfate. When preparing electronic-grade nickel sulfate, other metal ions except nickel ions are metal impurities, and nickel sulfate solution is used as the solution used for the tertiary cleaning in the activated carbon impurity removal, so as to ensure that other metal impurities are removed as much as possible, avoid introducing new metal impurities in the degreasing step of the electronic-grade nickel sulfate, and ensure a good TOC removal effect; when preparing electronic-grade manganese sulfate, other metal ions except manganese ions are metal impurities, and manganese sulfate solution is used as the solution used for the tertiary cleaning in the activated carbon impurity removal, so as to ensure that other metal impurities are removed as much as possible, avoid introducing new metal impurities in the degreasing step of the electronic-grade manganese sulfate, and ensure a good TOC removal effect; when preparing electronic-grade zinc sulfate, other metal ions except zinc ions are metal impurities, and zinc sulfate solution is used as the solution used for the tertiary cleaning in the activated carbon impurity removal, so as to ensure that other metal impurities are removed as much as possible, avoid introducing new metal impurities in the degreasing step of the electronic-grade zinc sulfate, and ensure a good TOC removal effect.

[0117] In the embodiments of the present invention, different activated carbon impurity removal methods are used for the preparation of different electronic-grade sulfates, that is, corresponding sulfate solutions are used for three-stage cleaning, which is beneficial to remove other metal impurities except the metal salt ions of the sulfate as much as possible, avoid the introduction of new metal impurities in the oil removal step of the electronic-grade sulfate, and ensure a good TOC removal effect.

[0118] In summary, the present invention adopts a three-stage cleaning method to remove impurities from the activated carbon raw material, and the total metal impurity content of the obtained activated carbon is low. It has a good effect when used in the preparation process of electronic-grade sulfate, especially it can achieve a good TOC removal effect. The activated carbon obtained by the impurity removal method of the present invention has a wide range of applications in the preparation of high-purity electronic-grade sulfate.

Claims

1. A method for removing impurities from activated carbon, characterized in that: The following steps are involved: S1. Primary cleaning: Use dilute sulfuric acid to clean the activated carbon raw material and soak it for 20 to 30 hours to obtain primary activated carbon; S2. Secondary cleaning: using ultrapure water to clean the primary activated carbon to obtain secondary activated carbon and a washing liquid, wherein the conductivity of the washing liquid is ≤10 μS; S3, tertiary cleaning: washing the secondary activated carbon with a sulfate solution to obtain activated carbon and sulfate washing solution after impurities are removed, wherein the difference between the total content of metal impurities in the sulfate washing solution and the total content of metal impurities in the sulfate solution is ≤30 μg / L; the metal impurities include other metal elements except the metal elements in the sulfate; In step S3, the sulfate includes copper sulfate, cobalt sulfate, nickel sulfate, manganese sulfate or zinc sulfate; In step S3, the metal ion concentration of the sulfate solution is 50-80 g / L.

2. The impurity removal method according to claim 1, characterized in that: In step S1, the activated carbon is wood activated carbon; And / or, in step S2, the conductivity of the ultrapure water is ≤1 μS; And / or, in step S2, the total content of metal impurities in the ultrapure water is ≤10 μg / L.

3. Activated carbon obtained by the impurity removal method according to any one of claims 1 to 2.

4. Use of the activated carbon according to claim 3 in the preparation of electronic grade sulfate.

5. A method for preparing electronic grade sulfate, characterized in that: The following steps are involved: Passing the crude sulfate solution through an activated carbon column containing the activated carbon of claim 3 to remove oil and obtain a sulfate deoiled liquid; The sulfate deoiling liquid is subjected to crystallization treatment to obtain the electronic grade sulfate.

6. The preparation method according to claim 5, characterized in that: During oil removal, the residence time of the crude sulfate solution in the activated carbon column is 0.6 to 5 hours.

7. The preparation method according to claim 5, characterized in that: During degreasing, the pH value of the crude sulfate solution is 2-5.

8. The preparation method according to claim 5, characterized in that: The activated carbon is granular activated carbon, and the average particle size of the granular activated carbon is 0.5 to 3 mm.

Citation Information

Patent Citations

  • Activated carbon pretreatment method and metal recovery method

    JP2020169365A